Altitudes AD and BE of a triangle ABC are such that AE = BD. Prove that AD = BE.
Answers
Answer:
Step-by-step explGiven AD and BE are altitude and AC = BC , S
Here
∠ BEA = ∠ BEC = 90° --------------- ( 1 )
And
∠ ADB = ∠ ADC = 90° ---------------- ( 2 )
So from equation 1 and 2 , we can say
∠ BEA = ∠ ADB = 90° ---------------- ( 3 )
And As given ABC is a isosceles triangles so , from base angle theorem ,we can say that
∠ CAB = ∠ CBA ----------------- ( 4 )
Now In ∆ BAE and ∆ ABD
∠ BEA = ∠ ADB ( From equation 3 )
∠ EAB = ∠ DBA ( As ∠ CAB = ∠ EAB ( same angles ) And ∠ CBA = ∠ DBA ( same angles ) And from equation 4 we know ∠CAB = ∠ CBA )
And
AB = AB ( Common side )
Hence
∆ BAE ≅∆ ABD ( By AAS rule )
So,
AE = BD ( By CPCT rule )
hence proved..
Answer:
Answer:
Step-by-step explGiven AD and BE are altitude and AC = BC , S
Here
∠ BEA = ∠ BEC = 90° --------------- ( 1 )
And
∠ ADB = ∠ ADC = 90° ---------------- ( 2 )
So from equation 1 and 2 , we can say
∠ BEA = ∠ ADB = 90° ---------------- ( 3 )
And As given ABC is a isosceles triangles so , from base angle theorem ,we can say that
∠ CAB = ∠ CBA ----------------- ( 4 )
Now In ∆ BAE and ∆ ABD
∠ BEA = ∠ ADB ( From equation 3 )
∠ EAB = ∠ DBA ( As ∠ CAB = ∠ EAB ( same angles ) And ∠ CBA = ∠ DBA ( same angles ) And from equation 4 we know ∠CAB = ∠ CBA )
And
AB = AB ( Common side )
Hence
∆ BAE ≅∆ ABD ( By AAS rule )
So,
AE = BD ( By CPCT rule )
hence proved.